Creating a profession of educators with the living-theories of master and doctor educators. (January 2016) - Whitehead, Jack; Huxtable, Marie
In our last paper in GEI we presented an argument for teachers to engage in Living Educational Theory research as Continuing Professional Development. In this paper we extend our analysis to show how this can empower educators to improve their practice and, by offering as a gift the knowledge they generate in the process, contribute to the creation of a profession of educators. The extension is grounded in the idea of enhancing professionalism in education through recognising and accrediting accounts of living-educational-theories as knowledge generated by professional practitioners as master and doctor educators. We distinguish Living Educational Theory research from a living-educational-theory. Living Educational Theory research refers to the conceptual principles that distinguish the research approach. A living-educational-theory is a values-based explanation offered by an individual of their educational influence in their own learning, the learning of others and the learning of social formations. It is argued that for this knowledge to be legitimated by universities, in the form of accredited awards, an extension and transformation will be required in the dominating forms of knowledge. It is also argued that educators teaching in continuing professional development programmes need to develop their talents, knowledge and expertise by researching their own practice in the same way as the teachers they are supporting. In doing so they exemplify an educational pedagogy appropriate to providing gifted education internationally for students of any age.